Using comics to improve english learners’ reading comprehension through task-based learning approach at Centro de Lenguas y Culturas, Universidad del Valle (2025)
Teaching English as a foreign language (EFL) requires a creative and effective approach to reinforcing reading comprehension in EFL learners. Reading comprehension is challenging because it requires the ability to understand and interpret written text. One valuable approach is the use of comics, recognized for their ability to combine text and visuals, making language acquisition engaging and accessible. This study explored the role of comics in improving reading comprehension among English learners at a language institute through action research, involving interviews, surveys, and observations. The findings revealed that integrating comics into language instruction significantly boosted students' reading comprehension, vocabulary acquisition, and engagement. Additionally, comics fostered cultural awareness by allowing students to reflect on diverse narratives.